Universal circularly polarized antenna for satellite communication systems - Sheersha, Jils Annie (2018)
The global navigation satellite systems (GNSSs) have been utilized in numerous areas such as positioning, mapping, public safety, surveillance, navigation, time standards, geographic studies, weather, and atmospheric information. The GNSS is a constellation of more than 100 satellites chiefly made out of Medium Earth Orbit (MEO) satellites including GLONASS, GPS, Galileo, and Compass. Also, the constellation is increased by Geostationary Orbit (GEO) satellites from QZSS and Compass. To cover whole GNSS band, wideband or dual-band circularly polarized antennas are required. A narrowband microstrip square patch antenna with an asymmetric metasurface is presented. The single fed antenna provides a circular polarization with an axial ratio less than 3dB. This is a unique model which generates circular polarization without using a slotted/slit/truncated patch antenna or multiple-feeding techniques. The asymmetric metasurface introduced below the patch helps to achieve axial ratio less than 3dB. The circularly polarized antennas are able to offer a reliable system connection since the polarization of the antennas is always precisely aligned. The satellites, space vehicles, and mobile vehicles require a circularly polarized antenna to maintain a communication link with a receiver system.